PENGARUH PENGGUNAAN MULTIMEDIA BERBASIS KOMPUTER OLEH GURU PAK TERHADAP MINAT BELAJAR - Holong Sihombing (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
Abstract - The research aim was to determine the positive and significant effect between the use of computer-based multimedia on the learning interest of tenth-grade students of SMA Negeri 1 Pahae Julu in Academic Year 2018/2019. The research design was correlational research using descriptive and inferential statistic. The result of the analysis showed that Fcount=12,48Ftable=1,51, then H0 was rejected and Ha was accepted. The study concluded that there was a positive and significant effect of the use of computer-based multimedia by Christian Education teachers on learning interest of tenth-grade students of SMA Negeri 1 Pahae Julu in Academic Year 2018/2019 reached 23,72%. Based on the result of the study, it is suggested to Christian Education teachers to apply computer-based multimedia to increase student’s learning interest.Keywords: Multimedia  Computer-Based, Learning Intere